INCREASING THE TEMPO OF READING USING A COMPUTER SIMULATION - NAGY, Marek (Journal of Technology and Information Education, 2018)
The article presents an experimental method of training reading aloud in the third grade of primary education. Reading aloud is an important intermediate step towards reading comprehension and reflects the state of perception of words as a whole. Its typical measurable attribute is the reading tempo, the appropriate level of which is necessary, but not sufficient, as a condition for understanding the text. The low tempo is also a demotivating factor and discourages further reading "for joy". For training purpose it was used Multimedia Reader, where children read the text into the microphone and the computer automatically checks and evaluates the recording. During the reading, the simulation of their previous performance is visualized and they try to overcome it.
Keywords: Primary education; reading aloud; computer simulation.